2011
DOI: 10.1111/j.1095-8649.2011.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, morphometric, meristic and osteological evidence for two species of hake (Actinopterygii: Gadiformes: Merluccius) in Argentinean waters

Abstract: Morphologically, both classic and landmark-based morphometry and meristic analyses of 241 specimens of Merluccius, along with the re-examination of six paratype specimens of Merluccius hubbsi, the holotype and three paratypes of Merluccius patagonicus and the syntype of Merluccius australis revealed the presence of only two species of Merluccius in Argentinean waters. Internal structures (hyomandibula, urohyal and sagitta otolith) of M. hubbsi were compared to those reported for M. patagonicus and were shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
8
20
1
Order By: Relevance
“…hubb153.2) but branched between the clusters of Austral hakes and Pacific hakes. Likewise, M. tasmanicus 24 and M. polylepis from the Southern Ocean 32 had been proposed as synonymous of M. australis 6,29,30 . However, their phylogenetic status was much like the rest of morphotypes, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…hubb153.2) but branched between the clusters of Austral hakes and Pacific hakes. Likewise, M. tasmanicus 24 and M. polylepis from the Southern Ocean 32 had been proposed as synonymous of M. australis 6,29,30 . However, their phylogenetic status was much like the rest of morphotypes, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Also, meristic (see Fig. 1 from 23 ) and molecular analyses 29,30 showed that M. patagonicus could be synonymous with M. hubbsi and that M. tasmanicus could be synonymous with M. australis 31 . Taxonomic uncertainties are expected in closelyrelated species that show extensive overlap in morphological and meristic traits.…”
mentioning
confidence: 99%
“…The actual reasons for morphometric variation between populations are often fairly tough to describe. However, several studies have found variations because of the environmental conditions, geographic position, ecological change and sometimes human error during work on morphometric measurements and meristic counts (Cabral et al 2003 ; Díaz de Astarloa et al 2011 ; Chaklader et al 2016a ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the economic importance, biological, ecological and fishing aspects of M. hubbsi. The most recent contributions are on juvenile growth (BURATTI; SANTOS, 2010;LORENZO et al, 2011), foraging strategies (TEMPERONI et al, 2013;BELLEGGIA et al, 2014), systematics (DÍAZ-DE-ASTARLOA et al, 2011) and differences in reproductive aspects and larval development (BETTI et al, 2014;MACCHI et al, 2016). The majority of them came from the Argentina and none is related to use of otolith morphology and morphometry to ascertain geographic variation of the species.…”
mentioning
confidence: 99%